Parachute deformity of the tricuspid valve. Issue 4 (August 1979) - Milo, S; Stark, J; Macartney, F J; Anderson, R H
Abstract : A parachute deformity of the tricuspid valve occurred in a heart with atrioventricular concordance, double outlet right ventricle, and straddling mitral valve. Although to the best of our knowledge parachute deformity of the tricuspid valve has not previously been reported, in this case its presence was insignificant in relation to the other lesions.